2018
DOI: 10.1016/j.ydbio.2017.07.026
|View full text |Cite
|
Sign up to set email alerts
|

Regulation and phylogeny of skeletal muscle regeneration

Abstract: One of the most fascinating questions in regenerative biology is why some animals can regenerate injured structures while others cannot. Skeletal muscle has a remarkable capacity to regenerate even after repeated traumas, yet limited information is available on muscle repair mechanisms and how they have evolved. For decades, the main focus in the study of muscle regeneration was on muscle stem cells, however, their interaction with their progeny and stromal cells is only starting to emerge, and this is crucial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
135
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 158 publications
(153 citation statements)
references
References 166 publications
5
135
1
1
Order By: Relevance
“…Skeletal muscle is constantly renewed in response to injury, exercise, or muscle diseases. A population of resident stem cells (satellite cells) accounts for skeletal muscle plasticity, maintenance and regeneration [1][2][3]. The muscle progenitor satellite cells are mitotically and physiologically quiescent in healthy muscle; they are stimulated by local damage to proliferate extensively and form myoblasts that will subsequently differentiate and fuse to form muscle fibres.…”
Section: Abstract: Myoblast; Myostatin; Syndecan-4mentioning
confidence: 99%
“…Skeletal muscle is constantly renewed in response to injury, exercise, or muscle diseases. A population of resident stem cells (satellite cells) accounts for skeletal muscle plasticity, maintenance and regeneration [1][2][3]. The muscle progenitor satellite cells are mitotically and physiologically quiescent in healthy muscle; they are stimulated by local damage to proliferate extensively and form myoblasts that will subsequently differentiate and fuse to form muscle fibres.…”
Section: Abstract: Myoblast; Myostatin; Syndecan-4mentioning
confidence: 99%
“…Skeletal muscle is made up of large multi-nucleated, post mitotic fibers, that have a large reserve capacity to regenerate following injury (Baghdadi & Tajbakhsh, 2018;Dumont, Bentzinger, Sincennes, & Rudnicki, 2015;Fukada, 2018;Wosczyna & Rando, 2018). Skeletal muscle regeneration is driven by skeletal muscle stem cells (MuSCs), typically quiescent in uninjured muscle but following injury, leave G0, enter the cell cycle as myoblasts and expand as needed to repair muscle injuries.…”
Section: Introductionmentioning
confidence: 99%
“…We used notexin-induced muscle regeneration in Bin1x11-/-mice and observed a decrease in fiber crosssectional area at 14 and 28 days after the muscle damage associated with a reduced fusion index and eventually leading to a decrease in specific force recovery. A deficit in myofibers growth during early regeneration was previously linked to a defect in myoblast fusion (Millay et al 2014;Baghdadi and Tajbakhsh 2018). Additionally, BIN1 was abundant at the myotubes fusion sites (Klinge et al 2007) and C2C12 cells expressing antisense Bin1 showed an impaired myoblast fusion (Wechsler-Reya et al 1998).…”
Section: Bin1 Muscle-specific Isoforms and Muscle Regenerationmentioning
confidence: 99%